PENGALAMAN WISATAWAN MENGIKUTI COOKING CLASS DAN ANALISIS SWOT DI BALI FARM COOKING SCHOOL - Bagus Ketut Soma Antara, Ida; Septiyani, Sania; Ayu Eka Suwintari, I Gusti; Ayu Melistyari Dewi, I Gusti (Berajah Journal, 2024)
This research explores the experiences of tourists participating in cooking classes at the Bali Farm Cooking School. The data analyzed are tourist comments on TripAdvisor regarding "Bali Farm Cooking School" taken on December 21, 2023. The data is derived from tourist comments in 2023 totaling 30. The research findings indicate that the majority of tourists give a maximum rating, indicating a very satisfying experience. The positive experience involves tangible and intangible aspects. Tourists feel happy learning to cook, getting to know the local market, and gaining insights into Balinese community life. SWOT analysis is also used to identify internal and external factors to create internal and external strategies for the Bali Farm Cooking School.